Tax Avoidance Mediated by Constitutional Ownership as Moderating Variables - Feryal Amima Widadi; Bambang Subroto; Aulia Fuad Rahman (Faculty of Economic and Business, 2022)
This study analyzes Tax Avoidance Mediated by InstitutionalOwnership as a Moderating Variable. The analytical methodused is Partial Least Square (PLS), with a sample of seventysevenfood and beverage manufacturing companies listed on theIDX for 2014 - 2020. The findings of this study show thatthin capitalization, profitability, and return on assets (ROA) ontax avoidance are influenced by institutional ownership. Thiscondition is one of the challenging issues to overcome in termsof tax avoidance for manufacturing companies in the food andbeverage sector of the food and beverage sector listed on theIndonesia Stock Exchange. The results of this study can be usedas a reference in making decisions for company owners andmanagers. Before investing their shares, investors will evaluatewhether tax avoidance by the company will provide benefits toovercome the tax burden or vice versa.JEL Classification: H26, E43, D24, G32